The present and future availability of high-tech minerals in waste mobile phones: Evidence from China. (10th August 2018) - He, Pengwei; Wang, Chang; Zuo, Lyushui
Abstract: High-tech minerals are key raw materials in national strategic emerging industries. Waste mobile phones contain a variety of high-tech minerals. With rapid economic development and improvements in living standards, mobile phones are becoming one of the most commonly used electronic devices among all electrical and electronic products. Since 2004, China has been world's largest mobile phone-producing and phone-consuming country, and correspondingly, it has generated excessive waste. In this paper, the dynamic material flow method and the Weibull distribution are used to analyze the quantity of waste mobile phones generated and the quantities of the high-tech minerals they contain based on the differentiation between feature phones and smartphones. Additionally, future trends regarding high-tech minerals in waste mobile phones are predicted using a market supply A model. Our research results show an increasing trend of waste mobile phone generation, indicating that a considerable amount of the high-tech minerals they contain can be recycled. Finally, the following recommendations were proposed to further improve the management and development system of waste mobile phones in China: the development of a high-tech mineral data base is urgent; policies should be formulated and implemented by governments to improve the overall waste management system; the ecological design of products should be improved by manufacturers; dismantling and refining technologies should be enhanced by recycling companies to improve the recycling rate; and the public awareness of recycling should be strengthened. Highlights: Generation amount of waste feature phones and smartphones in China from 1987 to 2035 are estimated, respectively. The high-tech minerals contain in waste feature phones and smartphones in China from 1987 to 2035 are analyzed, respectively. Recommendations were proposed to improve the management and development system of waste mobile phones in China.